Improving Health Literacy Through the SIGAP DESA Program: Education on Maternal Anemia Prevention and Communicable Disease Control in Bagendit Village - Genialita Fadhilla; Harlena Pratama Putri; Doni Anshar Nuari (Indonesian Journal of Community Empowerment (IJCE), 2026)
Limited access to information and health services in rural areas triggers disparities in public health literacy, particularly regarding the risk of maternal anemia and the threat of infectious disease transmission. This community service program, titled "SIGAP DESA" (Siaga Ibu Hamil dan Penyakit Menular di Masyarakat Desa), aimed to improve health knowledge, awareness, and early screening of disease risks among residents of Bagendit Village. The program was attended by 50 participants. Interventions were conducted using a promotive approach via interactive PowerPoint-based lectures (covering maternal anemia, tuberculosis, measles, and basic immunization) and a preventive approach through free health screenings (blood pressure, blood glucose, cholesterol, and uric acid). The effectiveness of the education was measured using pre-test and post-test questionnaire instruments to assess participants' knowledge levels. The evaluation results showed a significant surge in health literacy, where participants with a good knowledge level increased from 24% to 86% post-education. The health screening successfully identified high-risk residents, who were immediately directed to the local community health center (Puskesmas) referral system. The SIGAP DESA program is proven to be effective in improving the knowledge of Bagendit Village residents and has successfully facilitated access to free health screening services for rural communities.